2022
DOI: 10.34178/jbth.v5i1.193
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Synthesis with Different Reducing Agents Characterized by UV-Visible Spectroscopy and FTIR

Abstract: This study aims to analyze the syntheses of gold nanoparticles with different reducing agents: Sodium Citrate and Sodium Borohydride. The syntheses were characterized by Ultraviolet-visible Spectroscopy and the Fourier Transform Infrared Spectroscopy, in which we evaluated the influence of the reducing agent and the reaction agitation. The test results indicated the presence of metallic gold and confirmed the formation of gold nanoparticles. Finally, we composed a table showing the differences between the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…AuNP can be manufactured via chemical and physical processes. The AuNP obtained from chemical methods is often conducted by using tetrachloroauric acid with sodium citrate, sodium borohydride or other toxic reagents as reducing and stabilizing agents for the synthesis process [ 12 , 13 ]. One study reported that the nanoparticles synthesized via green approaches demonstrated lower cytotoxicity than chemical methods [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…AuNP can be manufactured via chemical and physical processes. The AuNP obtained from chemical methods is often conducted by using tetrachloroauric acid with sodium citrate, sodium borohydride or other toxic reagents as reducing and stabilizing agents for the synthesis process [ 12 , 13 ]. One study reported that the nanoparticles synthesized via green approaches demonstrated lower cytotoxicity than chemical methods [ 14 ].…”
Section: Introductionmentioning
confidence: 99%